Joint delivery planning with time windows: a case study on supply chain in newspaper industry. (April 2019) - Jodinesa, M N A; Yuniaristanto,; Sutopo, W; Hisjam, M
Abstract: The newspaper industry has some special characteristics such as short delivery time that will affect the price of the product. Some the newspaper firms, mostly have the same agency area. Due to the distribution is considered one of the variables that have a relatively high cost, it is necessary to save the cost. Joint delivery is a way to reduce distribution costs. By joint delivery planning, the value of synergies is defined as the (percent) difference between the distribution costs in the original situation in which all firms perform individual distribution, and the distribution costs of all firms are piled up and the route scheme is prepared simultaneously. The calculation of distribution costs using Vehicle Routing Problem with Time Windows (VRPTW) approach and obtained a distribution cost savings of 7.61%.